Upaya Meningkatkan Percaya Diri Anak Usia 4-5 Tahun Dengan Metode Bermain Peran Di TK Mitra - Sholiha, Ina Ibna; Kurniawaty, Lia; Priendarningtyas, Ajeng (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Based on the various problems that arise, the focus of this research is to increase the self-confidence of children aged 4-5 years at Mitra Kindergarten. Increasing the self-confidence of children aged 4-5 years will be carried out through role playing methods. This research aims to test efforts to increase the self-confidence of children aged 4-5 years using role-playing methods. To obtain data, researchers conducted observations, interviews and documentation. During the observation, the researcher prepared an instrument grid and observation sheet.The research method used is classroom action research, researchers use the Kemmis and Mc Taggart classroom action research model. The research subjects were Mitra Kindergarten children in group A aged 4-5 years, consisting of 10 children, namely 4 boys and 6 girls. The success criteria for this research is 80% of the number of children in the Very Well Developing (BSB) category.The research results show that in the pre-cycle 60% were not yet developing (BB), 20% were starting to develop (MB), 20% were developing according to expectations (BSH), 0% were developing very well (BSB). In Cycle I 0% Not Yet Developed (BB), 10% Starting to Develop (MB), 40% Developing as Expected (BSH), 50% Developing Very Well (BSB). In Cycle II 0% Not Yet Developed (BB), 0% Starting to Develop (MB), 20% Developing as Expected (BSH), 80% Developing Very Well (BSB). This proves that the role playing method can increase children's self-confidence.